Synthesis And Characterization Of Metal Coupled Zno Nanomaterials With Plasmonic Effect - Soo, Sock Kuan (Universiti Sains Malaysia, 2017)
Despite of its unique properties, ZnO nanomaterials have limited usage in optoelectronic devices and bio-/chemical sensor as a consequence of relatively poor UV emission. The crystal defects of ZnO that produce visible light emission is believed the origin that reduce the intensity of UV emission drastically. In this research, the enhancement of near band edge emission of ZnO particles was achieved by localized surface-plasmon resonance effect through coupling with metal nanoparticles, such as Ni, Al, Ag, Fe, and Cu. Firstly, ZnO submicron rods were synthesized via sol-gel method using Zn(NO3)2.4H2O, (CH2).6N4 and (C6H9NO)n, whereas ZnO hexagonal nanodisks were synthesized via sol-gel method by Zn(CH3COO)2.2H2O, NH4OH and Al2(SO4)3. Since ZnO submicron rods have a better crystal quality and photoluminescent (Iuv/Ivis ratio: 1.58), they were used in subsequent phase of this project. Next, the effect of concentration of nickel nitrate on the luminescence property of ZnO submicron rods was studied. The result shows that ZnO submicron rods coated with 0.07 M NiNO3 has the best luminescence property, with their Iuv/Ivis ratio: 41.15. Lastly, the luminescence properties of ZnO submicron rods deposited by Ag, Cu, Al and Fe at same molarity of 0.07 M NiNO3 were compared. The result shows that ZnO submicron rods coated with 0.07 M NiNO3 has the best luminescence property amongst the metals, followed by Al (Iuv/Ivis ratio 26.11), Ag (Iuv/Ivis ratio 4.44) and Fe (Iuv/Ivis ratio 4.00). The deposition of Cu deteriorated the luminescence property of ZnO submicron rods with Iuv/Ivis ratio of 0.11.